Can The Pore Scale Geometry Explain Soil Sample Scale Hydrodynamic Properties? - Smet, Sarah; Beckers, Eléonore; Plougonven, Erwan; Léonard, Angélique; Degré, Aurore (Frontiers in Environmental Science, 2018)
For decades, the development of new visualization techniques has brought incredible insights into our understanding of how soil structure affects soil function. X-ray microtomography is a technique often used by soil scientists but challenges remain with the implementation of the procedure, including how well the samples represent the uniqueness of the pore network and structure and the systemic compromise between sample size and resolution. We, therefore, chose to study soil samples from two perspectives: a macroscopic scale with hydrodynamic characterization and a microscopic scale with structural characterization through the use of X-ray microtomography (X-ray µCT) at a voxel size of 21.5³ µm³ (resampled at 43³ µm³). The objective of this paper is to unravel the relationships between macroscopic soil properties and microscopic soil structure. The twenty-four samples came from an agricultural field (Cutanic Luvisol) and the macroscopic hydrodynamic properties were determined using laboratory measurements of the saturated hydraulic conductivity (Ks), air permeability (ka), and retention curves (SWRC). The X-ray µCT images were segmented using a global method and multiple microscopic measurements were calculated. We used Bayesian statistics to report the credible correlation coefficients and linear regressions models between macro- and microscopic measurements. Due to the small voxel size, we observed unprecedented relationships, such as positive correlations between log(Ks) and a µCT global connectivity indicator, the fractal dimension of the µCT images or the µCT degree of anisotropy. The air permeability measured at a water matric potential of -70 kPa was correlated to the average coordination number and the X-ray µCT porosity, but was best explained by the average pore volume of the smallest pores. Continuous SWRC were better predicted near saturation when the pore-size distributions calculated on the X-ray µCT images were used as model input. We also showed a link between pores of different sizes. Identifying the key geometrical indicators that induce soil hydrodynamic behavior is of major interest for the generation of phenomenological pore network models. These models are useful to test physical equations of fluid transport that ultimately depend on a multitude of processes, and induce numerous biological processes.